2021
DOI: 10.1021/acsbiomaterials.1c00276
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Enabled Therapeutic Delivery and Regenerative Medicine: Physical and Biological Perspectives

Abstract: The role of ultrasound in medicine and biological sciences is expanding rapidly beyond its use in conventional diagnostic imaging. Numerous studies have reported the effects of ultrasound on cellular and tissue physiology. Advances in instrumentation and electronics have enabled successful in vivo applications of therapeutic ultrasound. Despite path breaking advances in understanding the biophysical and biological mechanisms at both microscopic and macroscopic scales, there remain substantial gaps. With the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 142 publications
(265 reference statements)
0
4
0
Order By: Relevance
“…Such ultrasound triggers exploit the idea of using localised heat at the site of delivery which in turn discharge the cargo as the delivery system is disrupted (111). The product generated after the ultrasonic trigger interacts with the membrane of the liposome and releases drugs due to the peroxidation of unsaturated lipids present in the membrane (117).…”
Section: Microenvironment-specific Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such ultrasound triggers exploit the idea of using localised heat at the site of delivery which in turn discharge the cargo as the delivery system is disrupted (111). The product generated after the ultrasonic trigger interacts with the membrane of the liposome and releases drugs due to the peroxidation of unsaturated lipids present in the membrane (117).…”
Section: Microenvironment-specific Nanoparticlesmentioning
confidence: 99%
“… 111 The product generated after the ultrasonic trigger interacts with the membrane of the liposome and releases drugs due to the peroxidation of unsaturated lipids present in the membrane. 117 Such a strategy gives flexibility to regulate the concentration and extent of local anaesthesia release, also no other tissue injury was detected. 118 It was suggested that the sonosensitizer discharges ROS when an ultrasonic trigger was given to the liposome.…”
Section: Microenvironment-specific Nanoparticlesmentioning
confidence: 99%
“…[63][64][65][66] Compared with other stimulation conditions, ultrasonic triggering is noninvasive, safe, controllable, and economical, and thus deserves attention under novel triggering conditions. Currently, ultrasoundresponsive hydrogels, combining the characteristics of hydrogels and ultrasound, have made many outstanding achievements in biomedical applications, such as drug delivery, [67][68][69][70][71] biomedical imaging 64,72,73 and smart materials, [74][75][76][77] and shown increasingly powerful functions in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The physical, biological, and chemical effects of ultrasound-induced cavitation that enhance therapeutic outcomes. Adapted with permission [43]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%